The Impact of Government Debt and Debt Servicing on Economic Growth An empirical approach for Albania - Mera, Nertil; Ryskulov, Urmat (Richtmann Publishing, 2012)
As the government spending around the world have extremely increased, many economies are concerned about the negativeeffects that high levels of debt have on the economic growth. Many empirical studies show a non-linear relationship between debt andeconomic growth. This paper uses linear regression model to study the impact of government debt and external debt service oneconomic growth in Albania. By using historical data from 1991 to 2010 it shows the existence of a positive effect of internal debt andexternal debt on economic growth of Albania. In contrast if finds a negative relationship between external debt service and economicgrowth. Higher levels of external debt are accompanied with higher amounts of money flowing out of the country as a service to the debt.This negative impact of external debt service on economic growth derived from higher levels of external debt fosters the government toreduce the level of external debt through more consolidated monetary and fiscal policies.